Temporal Ultrasound Image Enhancement for Kidney Diagnosis - Othman, Pawan Shivan (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Ultrasound imaging enables the physician to view the tissues and organs in abdominal region of the body without hazards of ionization compared to the other radiation based internal organ inspection devices. It provides highly accurate imaging of a kidney on suspected acute renal diseases. This thesis proposes temporal filtering methods to enhance the ultrasound images from ultrasound kidney video for the purposes of identification and diagnosis of kidney diseases by processing consecutive images of the acquired kidney video extending the spatial mean, median and weighted mean image filters to temporal dimension after cropping and aligning the image frames manually in MATLAB by Image Processing Toolbox to suppress speckle noise, and improve information content for a diagnosis by a medical doctor. The assessment of the filtered images by 10 medical experts indicates that the proposed temporal mean, median, and weighted mean filters improve the images better than the common spatial mean, median and weighted mean filters. The evaluators ranked the temporal weighted mean filtered images as the least preferable, while they scored the temporal median filtered images as the best preferable ultrasound images for the purpose of renal diagnosis. Keywords: Ultrasound Kidney Image, Image Enhancement by Video, Temporal Mean filter, Temporal Median Filter, Temporal Weighted Mean Filter.

ÖZ: Bu tez böbrek hastalıklarının tanımlanması ve tıp doktorlarınca teşhisi amacıyla böbrek videosunda ardışık görüntüleri elle kırpma ve hizalama sonrasında işlemek üzere 2-boyutlu ortalama, medyan ve ağırlıklı-ortalama görüntü filtrelerini temporal boyuta genişleterek leke gürültüsünü bastıran zamansal filtreleme yöntemleri önermektedir. Matlab kullanılarak filtrelenmiş görüntülerin 10 tıbbi uzman tarafından değerlendirilmesi sonucu, önerilen temporal ortalama, medyan ve ağırlıklı ortalama filtrelerin, görüntüleri ortak mekânsal ortalama, medyan ve ağırlıklı ortalamalı filtrelerden daha fazla iyileştirdiğini gösteriyor. Filtrelenmiş görüntüleri böbrek teşhisi amacıyla değerlendiren uzman doktorlar, sıralamalarında temporal ağırlıklı ortalama filtrelenmiş görüntüleri en az tercih edilen olarak seçerken, temporal medyan filtrelenmiş görüntüleri en iyi tercih olarak seçtiler. Anahtar Kelimeler: Ultrason Böbrek Görüntüsü, Videodan Görüntü Geliştirme, Temporal Ortalama filtre, Temporal Medyan Filtre, Temporal Ağırlıklı Ortalama Filtre.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2017. Supervisor: Assoc. Prof. Dr. Mehmet Bodur.
Keywords: Computer Engineering; Ultrasonic imaging-Radiological and Ultrasound Technology; Medical Ultrasonography; Ultrasound Kidney Image; Image Enhancement by Video; Temporal Mean filter; Temporal Median Filter; Temporal Weighted Mean Filter